Analysis of NLR and MLR Values in Patients with Pulmonary Tuberculosis and Pulmonary Tuberculosis with Diabetes Mellitus - Rachmad Bayu Kuncara; Parisade Galih Sasangka; Anung Sugihantono; Iin Desmiany Duri; Nurul Qomariyah; Menik Kasiyati; Sresta Azahra; Wiwit Sulistyasmi (Poltekkes Kemenkes Tanjung Karang, 2025)
Tuberculosis (TB) infection can cause changes in hematological parameters such as neutrophils, monocytes, and lymphocytes. The neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR) are used as indicators of inflammation and immune response in infectious diseases, including TB. Diabetes mellitus (DM) as a comorbidity can exacerbate inflammation, potentially affecting NLR and MLR values in TB patients. This study aimed to determine the NLR and MLR values in patients with pulmonary TB and pulmonary TB with DM. This research used a quantitative observational design with a cross-sectional approach, involving 72 respondents from several primary health centers (Puskesmas) in Semarang City, divided into two groups of 36 individuals each. The sampling technique used was purposive sampling. The results showed that the mean NLR value in pulmonary TB patients was 2.20, and in pulmonary TB with DM patients was 2.89, with a significant difference (p=0.002). Meanwhile, the mean MLR value in pulmonary TB patients was 0.34 and in pulmonary TB with DM patients was 0.33, with no significant difference (p=0.752). These findings indicate that NLR is more sensitive than MLR in reflecting the inflammatory status and DM complications in TB patients. NLR can be used as an additional marker in the clinical monitoring of TB patients, especially those with DM comorbidity.